Toll-like receptor 4 and Syk kinase shape dendritic cell-induced immune activation to major house dust mite allergens - Busold, Stefanie; Akkerdaas, Jaap H.; Zijlstra-Willems, Esther M.; van der Graaf, Kees; Tas, Sander W.; de Jong, Esther C.; van Ree, Ronald; Geijtenbeek, Teunis B. H. (Frontiers in Medicine, 2023)
Background House dust mite (HDM) is a major cause of respiratory allergic diseases. Dendritic cells (DCs) play a central role in orchestrating adaptive allergic immune responses. However, it remains unclear how DCs become activated by HDM. Biochemical functions of the major HDM allergens Der p 1 (cysteine protease) and Der p 2 (MD2-mimick) have been implicated to contribute to DC activation. Methods We investigated the immune activating potential of HDM extract and its major allergens Der p 1 and Der p 2 using monocyte-derived DCs (moDCs). Maturation and activation markers were monitored by flow cytometry and cytokine production by ELISA. Allergen depletion and proteinase K digestion were used to investigate the involvement of proteins, and in particular of the major allergens. Inhibitors of spleen tyrosine kinase (Syk), Toll-like receptor 4 (TLR4) and of C-type lectin receptors (CLRs) were used to identify the involved receptors. The contribution of endotoxins in moDC activation was assessed by their removal from HDM extract. Results HDM extract induced DC maturation and cytokine responses in contrast to the natural purified major allergens Der p 1 and Der p 2. Proteinase K digestion and removal of Der p 1 or Der p 2 did not alter the immune stimulatory capacity of HDM extract. Antibodies against the CLRs Dectin-1, Dectin-2, and DC-SIGN did not affect cytokine responses. In contrast, Syk inhibition partially reduced IL-6, IL-12 and completely blocked IL-10. Blocking TLR4 signaling reduced the HDM-induced IL-10 and IL-12p70 induction, but not IL-6, while endotoxin removal potently abolished the induced cytokine response. Conclusion Our data strongly suggest that HDM-induced DC activation is neither dependent on Der p 1 nor Der p 2, but depend on Syk and TLR4 activation, which might suggest a crosstalk between Syk and TLR4 pathways. Our data highlight that endotoxins play a potent role in immune responses targeting HDM.